Diversity and effect of Trichoderma spp. associated with green mold disease on Lentinula edodes in China. Issue 4 (4th May 2016) - Wang, Gangzheng; Cao, Xiantao; Ma, Xiaolong; Guo, Mengpei; Liu, Changhao; Yan, Lianlian; Bian, Yinbing
Abstract: Lentinula edodes, one of the most important edible mushrooms in China, is affected heavily by the infection of green mold that overgrows mushroom mycelia. We collected the diseased samples from main L. edodes cultivation regions in China to characterize the pathogen and to study the effect of Trichoderma spp. on L. edodes species. We identified six Trichoderma species, that is, T. harzianum, T. atroviride, T. viride, T. pleuroticola, T. longibrachiatum, and T. oblongisporum based on the internal transcribed spacer or tef1‐ α sequences and morphology characteristics. In confrontation cultures on Petri plates or in tubes, and in L. edodes cultures in a medium containing Trichoderma metabolites, L. edodes mycelia were not only distorted and swollen, but also inhibited by Trichoderma isolates. It is not possible that adjusting pH value or temperature is used for controlling L. edodes green disease, because the growth of most of Trichoderma isolates and L. edodes shared similar pH and temperature conditions. Abstract : We collected Trichoderma species on L. edodes rot logs. They were identified as T. harzianum, T. atroviride, T. viride, T. pleuroticola, T. longibrachiatum, and T. oblongisporum based on the internal transcribed spacer or tef1‐ α sequences and morphology characteristics.